Rotating Machinery - Hailu, Getu (IntechOpen, 2020)
Rotating machinery or turbomachinery is a machine with a rotating component that transfers energy to a fluid or vice versa. Rotating machines are one of the most widely used machines. They are used in everyday life, at least once a day. We find a turbomachine (fan) in a hair dryer and in a computer. We find a turbomachine (pump) in a refrigerator. Other commonly used household machines are clothes washers and dish washers. These machines need to drain the dirty water and replace with clean water. To do so an important component of these machines is a pump that is used to remove the dirty water. A water pump (hydrodynamic pump) is also essential to our car?s operation by maintaining an optimum operating temperature of the engine. The pump ensures that the coolant keeps circulating through the engine block, hoses and radiator, and maintains an optimum operating temperature. Turbomachines are also key machines used in power generation, fluid transportation, the processing industry and energy conversion. This book presents recent developments in improving the aero-thermal performance and the efficiencies of rotating machines.